1998
DOI: 10.1002/(sici)1521-379x(199803)50:2/3<120::aid-star120>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Production of Erythritol by Newly Isolated Osmophilic Trichosporon sp.

Abstract: One strain of osmophilic Trichosporon sp. which produces highest amounts of erythritol, was isolated from honeycomb. This strain produced highest amounts of erythritol with total glucose utilization in fermentation medium at 35°C and a temperature of 30°C results in an insufficient glucose utilization and lower production of erythritol, but higher growth of cell mass as compared with fermentation temperature of 35°C. An efficient fermentation medium for production of erythritol by the strain was mixture of 30%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…2), which are superior to erythritol production of 142 g/L from Trichosporon sp. in a 500-L fermentor [9]. In addition, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2), which are superior to erythritol production of 142 g/L from Trichosporon sp. in a 500-L fermentor [9]. In addition, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9]. It has also been reported that Leuconostoc oenos produces erythritol, but only under anaerobic conditions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Several yeast genera have been used for erythritol production, namely Aureobasidium (Ishizuka et al, ), Trichosporonoides (Aoki, Pastore, & Park, ), Moniliella (Lin, Wen, Liau, & Chu, ), Trigonopsis (Kim, Lee, Kim, & Oh, ), Trichosporon (Park, Yook, & Park, ), Torula (Lee, Ha, Kim, & Oh, ), Candida (Ryu, Park, Park, Kim, & Seo, ), Pseudozyma (Jeya et al, ) and Yarrowia (Rymowicz, Rywińska, & Gładkowski, ) (Table ). In order to improve erythritol productivity or yield, some of these strains were modified genetically.…”
Section: Optimization Of Erythritol Productionmentioning
confidence: 99%
“…Aureobasidium (Ishizuka et al, 1989), Trichosporonoides (Aoki, Pastore, & Park, 1993), Moniliella (Lin, Wen, Liau, & Chu, 2001), Trigonopsis (Kim, Lee, Kim, & Oh, 1997), Trichosporon (Park, Yook, & Park, 1998b), Torula (Lee, Ha, Kim, & Oh, 2000), Candida (Ryu, Park, Park, Kim, & Seo, 2000), Pseudozyma (Jeya et al, 2009)…”
Section: Strain Improvementmentioning
confidence: 99%
“…As another example, butanetriol was characterized only in the methanol extract of propolis from T. angustula, and the cyclic polyhydroxy alcohol inositol was found only in the methanol extract of propolis from A. mellifera. Park et al (1998Park et al ( , 2001) isolated microorganisms from pollen of Mangifera sp. (Anacardiaceae) and from Brazilian honeys, which were able to convert sucrose, glucose and fructose to erythritol.…”
Section: Erythrose/erythritolmentioning
confidence: 99%